Study on the Origin and Fluid Identification of Low-Resistance Gas Reservoirs. (2nd December 2020) - Yuhui, Zhou; Qingxiong, Hu; Wentao, Liu; Zhiqi, Wu; Yule, Yan; Jialing, Ma
Abstract : The Wu 2 section of the Ke017 well block is a low-resistance gas reservoir with ultralow porosity and low permeability. The comprehensive analysis of rock lithology, physical properties, sedimentary characteristics, and gas content demonstrated that the development of micropores in illite/smectite dominated clay minerals together with the resulted additional conductivity capability and complex reservoir pore structures, as well as the enrichment of self-generating conductivity minerals like zeolites and pyrite which were the formation mechanisms of low-resistance gas layers in the Wu 2 section. A low-resistance gas reservoir has poor physical property, and it is difficult to distinguish the oil layer from the dry, gas, or water layers. In this paper, based on well/mud logging data and laboratory data, by taking advantages of the "excavation effect" of neutron gas and the dual-lateral resistivity difference between different depths, we successfully established a set of low-contrast log response methods for the identification and evaluation of oil layer and formation fluids. For a gas layer, the difference between neutron porosity and acoustic (or density) porosity is smaller than 0 and the difference in dual-lateral resistivity is greater than 0. For a water layer, the neutron porosity is similar to the acoustic (or density) porosity and the dual-lateral resistivity difference will be less than 0. While for a dry layer or a layer with both gas and water, the difference in porosity as well as dual-lateral resistivity is very small. The proposed method effectively solves the technical problem of oil layer and formation fluid identification in low-resistance gas reservoirs.